2016
DOI: 10.3390/ijms17111887
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterisation of a Reference Transcriptome for Lentil (Lens culinaris Medik.)

Abstract: RNA-Seq using second-generation sequencing technologies permits generation of a reference unigene set for a given species, in the absence of a well-annotated genome sequence, supporting functional genomics studies, gene characterisation and detailed expression analysis for specific morphophysiological or environmental stress response traits. A reference unigene set for lentil has been developed, consisting of 58,986 contigs and scaffolds with an N50 length of 1719 bp. Comparison to gene complements from relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 62 publications
6
47
0
Order By: Relevance
“…The final Doza assembly resulted in 58,962 transcripts with total assembly length of 66,959,534 bp (average length 1135.6 bp and N50 of 1595), whereas the final Farah assembly comprised of 53,275 transcripts with total assembly length of 60,943,125 bp (average length 1143.9 bp and N50 of 1683). Both the Doza and Farah assemblies contained a substantial number of large transcripts with sequence length >500 bp (average 67.3%), which was comparable to the results obtained by previous studies [40,50] with a deep sequencing method for transcriptome generation. These results are highly comparable to those for the transcriptomes of other legume species, such as M. truncatula, which has a total of 66,028,174 bp (M. truncatula Genome Project v. 4.0), and soybean, which has 68,278,578 bp [51], and much higher than that of chickpea, which has 32,973,966 bp [52].…”
Section: De Novo Transcriptome Assemblysupporting
confidence: 75%
See 4 more Smart Citations
“…The final Doza assembly resulted in 58,962 transcripts with total assembly length of 66,959,534 bp (average length 1135.6 bp and N50 of 1595), whereas the final Farah assembly comprised of 53,275 transcripts with total assembly length of 60,943,125 bp (average length 1143.9 bp and N50 of 1683). Both the Doza and Farah assemblies contained a substantial number of large transcripts with sequence length >500 bp (average 67.3%), which was comparable to the results obtained by previous studies [40,50] with a deep sequencing method for transcriptome generation. These results are highly comparable to those for the transcriptomes of other legume species, such as M. truncatula, which has a total of 66,028,174 bp (M. truncatula Genome Project v. 4.0), and soybean, which has 68,278,578 bp [51], and much higher than that of chickpea, which has 32,973,966 bp [52].…”
Section: De Novo Transcriptome Assemblysupporting
confidence: 75%
“…Based on the number of unigenes, it can be concluded that the Farah assembly is less fragmented (23.6%) than the Doza assembly (37.9%). The number of unigenes obtained from this study is highly comparable to those from other legume genomes including chickpea (28,269 gene models [52]) and lentil (27,396 unigenes based on the Nr database [50]). Moreover, BLASTX analysis revealed that the largest number of matches were to M. truncatula (around 43% and 34% for Doza and Farah, respectively), followed by chickpea (approximately 22% for Doza and 16% for Farah), and then any other plant species.…”
Section: Annotation Of the Transcriptome Assembliessupporting
confidence: 54%
See 3 more Smart Citations